Strategi Guru Dalam Mengintegrasikan Pendidikan Karakter Melalui Kurikulum Pendidikan Agama Islam - Nabilul Fikri Solahuddin Azzaki; Muhammad Dimas Aulia Rohman; Muhammad Fadil Afandi (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2025)
Character education through the Islamic Religious Education (PAI) curriculum has a vital role in shaping a young generation that is not only academically intelligent, but also noble. This study aims to explore the strategies used by teachers in integrating character values into the Islamic Education learning process. The research method used is qualitative with a field study approach, involving interviews, observations, and document analysis in several elementary schools and madrasahs. The results showed that effective strategies include teacher exemplary, habituation of good behavior, use of active learning methods, positive attitude and behavior-based assessment, and collaboration with parents. Teacher example is a key factor in inspiring students to apply character values. Habituation of good behavior through daily routines helps students internalize the values. In addition, active learning methods allow students to be directly involved in the learning process, while character-based assessments encourage students to demonstrate positive attitudes. Parental involvement is also important to create harmony between education at school and at home. Despite challenges such as the lack of understanding of character education among teachers and academic pressures, this study confirms the importance of integrating character education in the PAI curriculum to produce a generation that is faithful, pious and virtuous according to Islamic teachings.